Działalność inwestycyjna polskiego sektora MŚP po przystąpieniu do Unii Europejskiej - Duda, Joanna (Investment Activity of the Polish SME Sector After the Accession of the European Union, 2007)
Even though the Polish SME sector has been encountered a lot of barriers limiting its access to outer financing sources, some positive changes could be observed after Poland's accession to the European Union. Most of investment decisions which were made had an innovative character, what should have a positive influence on the competitiveness of the firms on the European market. However, a lot of SME firms didn't make any investment decisions. In this paper, the investment activity of the Polish SME sectors between 2004 and 2005 has been described on the basis of empirical research results.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 79-86